8-oxodG accumulation within super-enhancers marks fragile CTCF-mediated chromatin loops. Issue 6 (2nd March 2022) - Scala, Giovanni; Gorini, Francesca; Ambrosio, Susanna; Chiariello, Andrea M; Nicodemi, Mario; Lania, Luigi; Majello, Barbara; Amente, Stefano
Abstract: 8-Oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG), a major product of the DNA oxidization process, has been proposed to have an epigenetic function in gene regulation and has been associated with genome instability. NGS-based methodologies are contributing to the characterization of the 8-oxodG function in the genome. However, the 8-oxodG epigenetic role at a genomic level and the mechanisms controlling the genomic 8-oxodG accumulation/maintenance have not yet been fully characterized. In this study, we report the identification and characterization of a set of enhancer regions accumulating 8-oxodG in human epithelial cells. We found that these oxidized enhancers are mainly super-enhancers and are associated with bidirectional-transcribed enhancer RNAs and DNA Damage Response activation. Moreover, using ChIA-PET and HiC data, we identified specific CTCF-mediated chromatin loops in which the oxidized enhancer and promoter regions physically associate. Oxidized enhancers and their associated chromatin loops accumulate endogenous double-strand breaks which are in turn repaired by NHEJ pathway through a transcription-dependent mechanism. Our work suggests that 8-oxodG accumulation in enhancers–promoters pairs occurs in a transcription-dependent manner and provides novel mechanistic insights on the intrinsic fragility of chromatin loops containing oxidized enhancers-promoters interactions.